(E)-N-(3,3-Diphenylallylidene)-2-(trifluoromethyl)aniline - Yu, B.-Y.; Lee, J.E.; Cho, Y.S.; Cha, J.H.; Lee, J.K. (2013)
In the title compound, C22H16F3N, the C=N bond of the central imine group adopts an E conformation. The dihedral angles between the 2-(trifluoromethyl)phenyl ring and the benzene rings are 9.34 (1) and 68.8 (1)°. The imine group displays a C - C - N=C torsion angle of 41.6 (3)°. In the crystal, weak C - H？F hydrogen bonds link the molecules into chains parallel to the b-axis direction.